Driving test management system / Aida Che Aziz - Che Aziz, Aida (2016)
Driving Test Management System is a system being developed to facilitate Road Transport Department (JPJ) the operation of the driving license test. Driving license test procedures in Malaysia currently run manually where is using form system. This project built to smooth running of the driving license test process where is in this system, the JPJ Officer only need to access the driving license test system on smart phone for replace form system. Using this system, process of driving test quite faster than manually because the JPJ Officer only tick on checklist application. Then, the system will generate marks and automatically all data of results will be record on database. While Driving Test Management System also developed to facilitate Staff Driving School manages of the candidate where this system is involves the process of registration process, driving license test process and driving license test result process. Besides that, this system provided service for the driver class license D and B2. This system adopts Waterfall model in its development. The technologies for developed system use Ubuntu 14.04 while the framework used in this system is Yii2.0. The PHPmyAdmin as a database and Sublime is a source code editor. In future, it is hoped the driving test process will be based on this system.